The role of innovative systems in a small and medium enterprise - Piersiala, Luiza; Kapler, Monika (Ekonomia i Prawo. Economics and Law, 2023)
Motivation: The considerations contained in the article concern the issues of innovation in information systems of small and medium-sized enterprises. The results of the research on barriers faced when introducing innovation in the surveyed economic entities were presented. The focus was on the analysis of internal financial barriers. Aim: The purpose of the article is to identify and analyze the internal barriers resulting from the implementation of innovative information systems and their impact on the management of small and medium-sized enterprises. Results: The results of the analysis indicate that the dominant innovations in information systems implemented in the surveyed enterprises are innovations in the area of information systems supporting finance and accounting.